2003
DOI: 10.1080/01926230390213775
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Histochemical Staining Method to Identify Hyaline Droplets in the Rat Kidney

Abstract: Hyaline droplet formation in the proximal tubular cells of the kidney commonly occurs under different pathological conditions in experimental animals. In rats, intracytoplasmic hyaline droplet formation is predominantly associated with accumulation of the male rat-specific alpha(2u)-globulin, whereas under other (pathological) conditions (eg, histiocytic sarcoma and chronic progressive nephropathy [CPN]) other proteins are involved. Staining methods to visualize hyaline droplets either need plastic embedded ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Likewise, in the kidneys of all treated males eosinophilic cytoplasmic droplets were present, with a dose-dependent shift to higher grades. In a supplementary study the kidney slides of exclusively male rats were stained also with Mallory Heidenhain stain , which results in enhanced staining of the cytoplasmic droplets (De Rijk et al, 2003;Frazier et al, 2012); this confirmed the observations of the eosine staining. An increased hyaline droplet accumulation in male rats exclusively is characteristic of α 2u -globulin nephropathy (Hard et al, 1993), which is considered a male rat specific effect with little relevance for humans.…”
Section: -Day Study On β-Caryophyllene [Fl-no: 01007]supporting
confidence: 69%
“…Likewise, in the kidneys of all treated males eosinophilic cytoplasmic droplets were present, with a dose-dependent shift to higher grades. In a supplementary study the kidney slides of exclusively male rats were stained also with Mallory Heidenhain stain , which results in enhanced staining of the cytoplasmic droplets (De Rijk et al, 2003;Frazier et al, 2012); this confirmed the observations of the eosine staining. An increased hyaline droplet accumulation in male rats exclusively is characteristic of α 2u -globulin nephropathy (Hard et al, 1993), which is considered a male rat specific effect with little relevance for humans.…”
Section: -Day Study On β-Caryophyllene [Fl-no: 01007]supporting
confidence: 69%
“…268 Moreover, the capacity for renal protein handling in males is less than in females. 273 Ultrastructural examination reveals membrane-bound bodies often containing crystalloid structures composed of arrays of an ordered electron-dense lattice with distinct periodicity, features suggestive of crystalline protein (Figure 10.6b). 269 Although humans excrete proteins of a similar nature, they are found in only trace amounts.…”
Section: Hyaline Dropletsmentioning
confidence: 99%
“…Formalin-fixed kidney and liver samples were processed routinely into paraffin, sectioned at 3 mm and stained with haematoxylin and eosin (H&E). Kidney samples were also stained with chromotrope-aniline-blue (CAB; De Rijk et al, 2003). Kidney and liver sections were examined microscopically; in the kidneys, degenerative lesions (H&E sections) were graded on a scale of 1-5, and hyaline droplet formation (CAB sections) on a scale of 1-3.…”
Section: Tissue Processingmentioning
confidence: 99%